Crowdsourcing jurídico como construção de conhecimento jurídico: aplicações no direito pátrio - DAMASCENA, Amanda Saraiva (2024)
This article analyzes the institute of crowdsourcing in the construction of legal knowledge, considering the new global paradigm of inserting technological tools and forms of logic into the legal field, in order to improve its procedures and achieve fairer and more uniform decisions. Thus, its main objective is to conceptualize crowdsourcing, together with the beginning of the discussion on its possible forensic applications. For this analysis, a survey of bibliographic and case law material was carried out; afterwards, the material was cataloged by topic and fiched; and finally, the written production, dividing the article into three parts. Using the deductive method, the study begins with the conceptualization of crowdsourcing, going through the historical structuring of the term and contextualizing its origin. Next, considering the agreed concept and focusing on the subject in the legal field, we analyze its application in the various branches of law, paying 1 attention to foreign legal systems and its emergence in the Brazilian legal system. Focusing on civil procedural law, we examine its use in the multi-door conflict system, looking at possible applications that are in line with the principles of self-composition, the participation of the parties and the search for balance and cohesion in conflict resolutions, whether pre-procedural or in the form of litigation. The conclusion is that the model of obtaining knowledge through the cooperation of agents from different social contexts implies an expansion of democratic judicial construction with broad popular participation, with legal crowdsourcing establishing itself as a new gateway for resolving conflicts and ensuring greater effectiveness of legal protection. As a result applied to civil procedural law, it is plausible to directly relate this institute to that of the amicus curiae, pointing to the structuring of a pre-procedural third-party intervention whose purpose is to standardize conflict resolutions obtained through self-compositional methods.